Evaluating poultry fat and crude palm oil blends on growth performance, fatty acid profile, lipid metabolism and antioxidant capacity in juvenile Asian seabass (Lates calcarifer) - Izzah, Husna Shafin; Karim, Murni; Yong, Annita Seok Kian; Loh, Jiun Yan; Yan, Chen; de Cruz, Clement R. (Elsevier B.v., 2026)
The high cost and limited availability of fish oil (FO) remain major challenges for formulating nutrient-rich and sustainable aquafeeds. This study investigated the complete replacement of FO with crude palm oil (CPO) and poultry fat (PF) blends in juvenile Asian seabass (Lates calcarifer), focusing on growth, muscle fatty acids, lipid metabolism and antioxidant capacity. A total of 216 juveniles (initial weight 4.8 ± 0.10 g) were randomly assigned to six dietary treatments. Isonitrogenous and isolipidic diets were formulated with varying CPO:PF ratios (CPO100, CPO75:PF25, CPO50:PF50, CPO25:PF75, PF100), and FO100 was used as the control. Growth performance and feed efficiency did not differ significantly among diets. Compared with the control diet, higher CPO and PF inclusion increased saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and n-6 fatty acids while reducing n-3 polyunsaturated fatty acids (PUFA) and the n-3 to n-6 ratio (P < 0.05). Serum triglyceride (TG) was elevated in CPO75:PF25 relative to control, and PF100 enhanced superoxide dismutase (SOD) activity. Other liver enzymes and oxidative stress markers were unaffected. Overall, these findings demonstrate that CPO and PF can substantially reduce dependence on fish oil as a supplemental lipid source in Asian seabass diets without adverse effects on growth or health. Nevertheless, given the observed decline in muscle n-3 long-chain polyunsaturated fatty acids, the application of a short-term fish oil finishing diet may be necessary to optimise final fillet nutritional quality for human consumption.